Operationalization of the “Online Generation” phenomenon - R. G. Smirnov (Цифровая социология)
The problem of definition and operationalization of the “Online Generation” phenomenon has been discussed in the article. Based on the classical and modern approaches to determining the age boundaries of young people and based on socio-cultural characteristics of the modern young generation, the age boundaries of “Online Generation” have been proposed. “Online Generation” is the generation of modern youth whose socialization and maturation took place under the direct influence of Internet-culture and onlinecommunications.Assumptions about such socio-psychological features of “Online Generation” as: the desire to prolong “social youth”, the lack of desire to take responsibility, etc., – have been made. In addition, the  phenomenon of “dematerialization of events” in the digital era has been revealed, when events, even large-scale and significant, having acquired the character of information lines, are being squeezed out of discourse (including from youth discourse), become “fundamentally distant” events that are no longer relevant to the present.Analyzing the problem of “Online Generation” through the prism of the conflict of “fathers and children”, the author has come to the conclusion that the values of youth from 2010–2019 will be able to meet the values expected by society only if the society itself, its social, economic and political systems will correspond to the collective values required of modern youth. In other words, young people will be able to meet the declared ideals of pioneers and Komsomol members only in a planned economy, and when the country’s political system will correspond to the system of political system in the USSR, which is impossible in today’s conditions.